Study on Durability of the Concrete of Sanitation Network in Ouargla Algeria Under the Existence of Sulphates Attack - Mohammed Amin Boumehraz; Mekki Mellas; Abdelouahed Kriker (Indonesian Journal of Science and Technology, 2018)
Abstract: Several degradations were noted on remediation networks (pipes and manholes) in the Ouargla - Algeria, due to the product quality concrete the type of pipe used, and  the aggressive of external environment. The objective of this research was to investigate the durability of pipes for sanitation networks in the Ouargla under the effect of sulfates (in particular H2S). In this research, the concrete specimens were conserved in real environment and these results were compared with the result of specimens control. They conclude the decrease in conservation of concrete specimens by 3% for compressive strength after 365 days. For concrete specimens exposed to H2S gas, a rapid deterioration after 90 days. Then, the change was found for from 90 to 365 days reduction to 40 % for compressive strength.